EFEKTIVITAS ADMINISTRASI PESERTA DIDIK TERHADAP KUALITAS PENDIDIKAN ANAK USIA DINI DI RA KARTINI 09 BUMIAJI BATU-MALANG - Athalia Tri Wastiqah; Muslikah; Eko Setiawan (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2024)
This study is based on the effectiveness of student administration on the quality of early childhood education. This study focuses on student administration, with the aim of knowing the management of student administration on the quality of early childhood education at RA Kartini 09 Bumiaji. The research used a qualitative research approach with a qualitative phenomenological research type. Data collection techniques used observation/surveys, interviews, and documentation. Data analysis used data triangulation. The results of the study showed that student administration management plays an important role in the quality of early childhood education, as evidenced by the increasing number of students, increasing facilities and infrastructure and increasing the welfare of educators and education personnel at the institution. The quality of education presented is based on national education standards. In addition, the effectiveness of data management is carried out very well. The conclusion of the study is that data administration is carried out according to the needs of the institution's management. Also, the evaluation process is carried out periodically. Thus, the effectiveness of student administration will always be evaluated to improve the quality of early childhood education in the long term. In addition, the welfare of early childhood education teachers is an important point that needs to be considered by the Ministry of Education in Indonesia.